Assessing the impact of understory vegetation cut on soil epigeic macrofauna from a cork-oak Montado in South Portugal - Mendes, Sara Margarida; Santos, Joaquim; Freitas, Helena; Sousa, José Paulo (Agroforestry Systems, 2011)
Cork oak ‘‘Montados’’ are a particular Mediterranean ecosystem, which can be found in Southern Portugal. Portuguese ‘‘Montados’’ are manmade ecosystems, mainly used for cork production and cattle farming, that support a high biological diversity. Current sustainable management techniques imply a shrub clearing with heavy machinery, which can be highly disruptive for soil biota. In order to evaluate the effects of understory vegetation management on soil epigeic macrofauna, ﬁve zones were deﬁned along a chronosequence of shrub clearing: a non-disturbed zone (zone 5) and zones where understory vegetation was cut at 4–5 years (zone 4), at 3–4 years (zone 3), at 2 years (zone 2) and at 1 year (zone 1). A sixth zone (zone 6) was selected in a pasture, where cattle are occasionally present. Soil fauna was sampled using ‘‘pitfall’’ traps and sampling took place in autumn 2003. A total of 2,677 individuals, separated into 152 species and morphospecies, were caught in the traps. With the exception of zone 6, that presented a lower number of species, all the other zones from the chronosequence presented, in most cases, a similar number of taxa, species diversity (Shannon) and species richness (Margalef). Multivariate analysis separated recently disturbed zones (plus zone 6) from those intervened at longer time; groups like Formicidae, Scydmaenidae, most families from Araneae and insect larvae appeared closely associated to zones 3–5 (with a higher shrub cover and thick litter layers), whereas, other Hymenoptera, Gastropda and most Coleoptera families, appeared associated to recently disturbed zones (zones 1 and 2) and to zone 6, characterized by a lower shrub cover and a lower accumulation of litter. This separation indicates that effects of the intervention can endure for 2 or 3 years. After that time, the normal natural regeneration of the understory vegetation seems to support the restoration of the macrofauna community, thus indicating that the sustainable management strategy adopted, i.e., making a shrub cut every 5–6 years, seems not induce a signiﬁcant effect on local species richness of soil epigeic macrofauna.
Keywords: Biodiversity; cork-oak forests; soil macrofauna; sustainable management; understory management

Forests of the Mediterranean region: gaps in knowledge and research needs - Scarascia-Mugnozza, Giseppe; Oswald, Helfried; Piussi, Pietro; Radoglou, Kalliopi (Forest Ecology and Management, 2000)
Mediterranean forests are characterised by a remarkable set of features that make them naturally and aesthetically attractive, on the one hand, but also quite fragile, on the other, therefore calling for careful strategies for their conservation and management. An exceptionally large variation of environmental conditions characterises the Mediterranean countries, where the environment can limit forest growth and succession but can also give rise, more often than it is supposed, to lush, mesic forest ecosystems, similar to those of central Europe. Moreover, Mediterranean forests contain an ample, plant and animal biological diversity, exempli®ed by the large number of tree species as compared to Nordic forests, and by their relatively high genetic variability due to the survival of many conifer and broadleaf species in southern European refuges, during the glacial periods. Another peculiar aspect of this region is the long-lasting manipulation of trees, forests and landscapes, since ancient times, with the diffusion all over the Mediterranean basin of such species as Pinus pinea, Cupressus sempervirens, Castanea sativa, and Quercus suber. The harsh and unpredictable climate, the dif®cult socio-economic conditions and the history of over-exploitation of the Mediterranean forests require that a scienti®cally sound conservation strategy and a locally-tailored sustainable management should be implemented. In particular, the need for identifying those silvicultural and management strategies appropriate for southern European forests should be stressed. Obviously, this consideration will have important effects on the de®nition of criteria for sustainability and eco-certi®cation. Also, social issues should be considered key factors for effective forest conservation in the Mediterranean region, otherwise it will be impossible to control forest ®res and landscape degradation. Based on these considerations a number of research priorities are discussed, with special consideration to possible impacts that global change may have on Mediterranean forest ecosystems.
Keywords: Biodiversity; forest ecosystems; Mediterranean Region; silviculture; sustainable management

Forests of the Mediterranean region: gaps in knowledge and research needs - Scarascia-Mugnozza, Giseppe; Oswald, Helfried; Piussi, Pietro; Radoglou, Kalliopi (Forest Ecology and Management, 2000)
Mediterranean forests are characterised by a remarkable set of features that make them naturally and aesthetically attractive, on the one hand, but also quite fragile, on the other, therefore calling for careful strategies for their conservation and management. An exceptionally large variation of environmental conditions characterises the Mediterranean countries, where the environment can limit forest growth and succession but can also give rise, more often than it is supposed, to lush, mesic forest ecosystems, similar to those of central Europe. Moreover, Mediterranean forests contain an ample, plant and animal biological diversity, exempli®ed by the large number of tree species as compared to Nordic forests, and by their relatively high genetic variability due to the survival of many conifer and broadleaf species in southern European refuges, during the glacial periods. Another peculiar aspect of this region is the long-lasting manipulation of trees, forests and landscapes, since ancient times, with the diffusion all over the Mediterranean basin of such species as Pinus pinea, Cupressus sempervirens, Castanea sativa, and Quercus suber. The harsh and unpredictable climate, the dif®cult socio-economic conditions and the history of over-exploitation of the Mediterranean forests require that a scienti®cally sound conservation strategy and a locally-tailored sustainable management should be implemented. In particular, the need for identifying those silvicultural and management strategies appropriate for southern European forests should be stressed. Obviously, this consideration will have important effects on the de®nition of criteria for sustainability and eco-certi®cation. Also, social issues should be considered key factors for effective forest conservation in the Mediterranean region, otherwise it will be impossible to control forest ®res and landscape degradation. Based on these considerations a number of research priorities are discussed, with special consideration to possible impacts that global change may have on Mediterranean forest ecosystems.
Keywords: Biodiversity; forest ecosystems; Mediterranean Region; silviculture; sustainable management

Analysis of dehesas with multiple use. Physical and economic indexes of sustainable management - Garcia, F P; SÁNCHEZ, M E; Diaz, F J M; Vega, A R D (BASIS OF THE QUALITY OF TYPICAL MEDITERRANEAN ANIMAL PRODUCTS, 1998)
The wide surface that dehesas hold in Spain, together with their economic, social and environmental importance, give enough justification to the researchs that widen the scientific knowlege about the economics of dehesa systems. However, the dehesa agroforestry farms do not appear in the different statistical documentary sources of the Agricultural Accounting Net. The lack of technical-economic data about these systems impede neither to observe the effects of the Common Agricultural Policy on the natural environment, nor to know as a whole the dynamics and structure of their flows and the stock of resources and income. This paper deals with the technical and economic management of dehesas in the field of the environmental economics. Its main aim has been to carry out an analytical case study. In order to develop it, four dehesa farms in the Southwest of the Badajoz Province were selected. These farms have collaborated on the development of the Research Project UE CAMAR CT 90-28 ``Technical and economic analysis of dehesa and montado systems{''}. Its importance lies in the basis of the case analysis, with a description of the systems and an identification of the structure and dynamics of their resources, either at physical and economic level.
Keywords: Dehesa; environmental econ; sustainable management

Analysis of dehesas with multiple use. Physical and economic indexes of sustainable management - Garcia, F. P.; Sanchez, M. E.; Diaz, F. J. M.; Vega, A. R. D. (BASIS OF THE QUALITY OF TYPICAL MEDITERRANEAN ANIMAL PRODUCTS, 1998)
The wide surface that dehesas hold in Spain, together with their economic, social and environmental importance, give enough justification to the researchs that widen the scientific knowlege about the economics of dehesa systems. However, the dehesa agroforestry farms do not appear in the different statistical documentary sources of the Agricultural Accounting Net. The lack of technical-economic data about these systems impede neither to observe the effects of the Common Agricultural Policy on the natural environment, nor to know as a whole the dynamics and structure of their flows and the stock of resources and income. This paper deals with the technical and economic management of dehesas in the field of the environmental economics. Its main aim has been to carry out an analytical case study. In order to develop it, four dehesa farms in the Southwest of the Badajoz Province were selected. These farms have collaborated on the development of the Research Project UE CAMAR CT 90-28 ``Technical and economic analysis of dehesa and montado systems{''}. Its importance lies in the basis of the case analysis, with a description of the systems and an identification of the structure and dynamics of their resources, either at physical and economic level.
The following values have no corresponding Zotero field: periodical: BASIS OF THE QUALITY OF TYPICAL MEDITERRANEAN ANIMAL PRODUCTS issue: 90 pub-location: POSTBUS 220, 6700 AE WAGENINGEN, NETHERLANDS
Keywords: Dehesa; environmental econ; sustainable management